2004
DOI: 10.1677/erc.0.0110149
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous enterochromaffin-like cell carcinomas in cotton rats (Sigmodon hispidus) are prevented by a somatostatin analogue.

Abstract: Among inbred female cotton rats (Sigmodon hispidus) 25-50% of the animals develop spontaneous gastric carcinomas; the corresponding figure for male cotton rats is approximately 1%. Animals with carcinomas have hypergastrinaemia and gastric hypo-anacidity and the tumours are derived from enterochromaffin-like (ECL) cells. The mechanism behind the hypo-anacidity is unknown. Carcinomas are found in all female cotton rats with hypergastrinaemia lasting more than 4 months and this represents an excellent animal mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The animals developing carcinomas were later found to have gastric hypoacidity, secondary hypergastrinemia, and pronounced ECL cell hyperplasia [42]. The oxyntic mucosa in hypergastrinemic cotton rats has marked hyperplasia of chromogranin A, synaptophysin, and HDC immunoreactive cells and a proportion of the tumour cells are chromogranin A, pancreastatin, HDC, and Sevier-Munger positive [42–45]with similar changes found in mRNA expression [46, 47]. Between the age of two and six months, a proportion of female cotton rats develop gastric hypoacidity by an unknown mechanism, and develop carcinomas after approximately four months of hypergastrinemia.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals developing carcinomas were later found to have gastric hypoacidity, secondary hypergastrinemia, and pronounced ECL cell hyperplasia [42]. The oxyntic mucosa in hypergastrinemic cotton rats has marked hyperplasia of chromogranin A, synaptophysin, and HDC immunoreactive cells and a proportion of the tumour cells are chromogranin A, pancreastatin, HDC, and Sevier-Munger positive [42–45]with similar changes found in mRNA expression [46, 47]. Between the age of two and six months, a proportion of female cotton rats develop gastric hypoacidity by an unknown mechanism, and develop carcinomas after approximately four months of hypergastrinemia.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Between the age of two and six months, a proportion of female cotton rats develop gastric hypoacidity by an unknown mechanism, and develop carcinomas after approximately four months of hypergastrinemia. Several studies have demonstrated the importance of gastrin in tumour development as carcinomas are prevented by injections of a gastrin receptor antagonist (YF476) [43], by removal of antral gastrin by antrectomy [48] or by administration of the somatostatin analogue octreotide [47]. Male cotton rats that are made hypergastrinemic due to either administration of loxtidine [49] or by partial corpectomy [50] also develop carcinomas in the oxyntic mucosa.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Animals developing carcinomas have gastric hypoacidity of an unknown cause and secondary hypergastrinemia [63] . The tumors develop from an oxyntic mucosa with marked hyperplasia of chromogranin A, synaptophysin and HDC-immunoreactive cells, and a proportion of the tumor cells are chromogranin A-, pancreastatin-, HDC-and Sevier-Munger-positive [63][64][65][66] . Carcinomas develop after 4 mo of hypergastrinemia, but are prevented by the gastrin receptor antagonist YF486 [64] , demonstrating gastrin is essential in carcinoma development in cotton rats.…”
Section: In Gastric Carcinogenesismentioning
confidence: 99%
“…The carcinomas can also be induced in male cotton rats by long‐term administration of the insurmountable H2 receptor antagonist loxtidine (5) as well as by partial corpectomy (6). The carcinoma development can be prevented by a gastrin‐receptor antagonist (4) or by a somatostatin analogue (7). The oxyntic mucosa surrounding spontaneous as well as induced carcinomas has a marked increase in chromogranin A (CgA)‐ and Sevier‐Munger‐positive cells, demonstrating hyperplasia of enterochromaffin‐like (ECL) cells (4, 7–9).…”
mentioning
confidence: 99%
“…The carcinoma development can be prevented by a gastrin‐receptor antagonist (4) or by a somatostatin analogue (7). The oxyntic mucosa surrounding spontaneous as well as induced carcinomas has a marked increase in chromogranin A (CgA)‐ and Sevier‐Munger‐positive cells, demonstrating hyperplasia of enterochromaffin‐like (ECL) cells (4, 7–9). We have argued that ECL cells lose expression of neuroendocrine markers during malignant transformation, explaining why only a proportion of the tumour cells are positive.…”
mentioning
confidence: 99%